2021
DOI: 10.1111/ajco.13565
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and cisplatin induction chemotherapy with or without fluorouracil in locoregionally advanced nasopharyngeal carcinoma: A retrospective propensity score matching analysis

Abstract: Purpose: To investigate whether the addition of fluorouracil to docetaxel and cisplatin induction chemotherapy (IC) can truly improve the prognosis of patients with locoregionally advanced nasopharyngeal carcinoma (NPC).Methods: A total of 801 patients newly diagnosed with non-metastatic locoregionally advanced NPC were included as the subjects. In this study, propensity score matching (PSM) was used for analysis of overall survival (OS), distant metastasis-free survival (DMFS), progression-free survival (PFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Our research showed that patients who received one cycle of IC had worse survival outcomes than those who received two or more cycles. Recently, two clinical retrospective studies found that the TPF regimen led to better 5‐PFS and DMFS survival in LA‐NPC patients than the PF or TP regimen, which was similar to our finding 34,43 . In addition to IC cycles and IC regimens, many studies have shown that a cumulative dose of 200 mg/m 2 cisplatin is optimal for treating patients with LA‐NPC 44–46 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our research showed that patients who received one cycle of IC had worse survival outcomes than those who received two or more cycles. Recently, two clinical retrospective studies found that the TPF regimen led to better 5‐PFS and DMFS survival in LA‐NPC patients than the PF or TP regimen, which was similar to our finding 34,43 . In addition to IC cycles and IC regimens, many studies have shown that a cumulative dose of 200 mg/m 2 cisplatin is optimal for treating patients with LA‐NPC 44–46 .…”
Section: Discussionsupporting
confidence: 87%
“…Recently, two clinical retrospective studies found that the TPF regimen led to better 5‐PFS and DMFS survival in LA‐NPC patients than the PF or TP regimen, which was similar to our finding. 34 , 43 In addition to IC cycles and IC regimens, many studies have shown that a cumulative dose of 200 mg/m 2 cisplatin is optimal for treating patients with LA‐NPC. 44 , 45 , 46 However, the optimal cumulative dose of cisplatin during radiotherapy after IC remains controversial, so we still regarded 200 mg/m 2 as the critical dose.…”
Section: Discussionmentioning
confidence: 99%